The exposure of the elderly to the news of the Corona pandemic TV and its reflection on their behavior: A survey study of a sample of the public of Baghdad governorate - Mohamed Ali Hussein, Walaa (ALBAHITH ALALAMI, 2022)
A Survey Study Of A Sample Of The Public Of Baghdad Governorate The current study aimed to identify the most prominent psychological and behavioral repercussions of the exposure of the elderly to the news of the Corona pandemic and to determine the mechanisms of their exposure. On an intended sample on both sides of (Al-Karkh and Al-Rasafa) and the simple random sample was adopted to choose the place of distribution of the questionnaire and the intentional sample. The research concluded several results, most TV news is still a primary source of information and that most of the sample move between stations to see more information about the pandemic and that the presentation of views confuses the elderly ،There are to side negative and positive cognitive aspect related to the perception of the pandemic as an international conspiracy against peoples The emotional reflection of exposure showed the presence of a state of anxiety، fear and panic Instability and a positive emotional reflection represented by a feeling of comfort, reassurance and stability. The behavioral results of the sample showed adherence to preventive measures, with most of the sample delinquent in unscientific behaviors as a result of the state of fear, panic and anxiety in which they live. Reassurance and stability The behavioral results of the sample showed adherence to preventive measures, with most of the sample delinquent in unscientific behaviors as a result of the state of fear, panic and anxiety in which they live.